Vertebral sarcoidosis with associated Darier-Roussy disease manifesting as acute back pain - Md Noh, Mohamad Syafeeq Faeez; Rajadurai, Naveen; Hassan, Thajunnisa; Alias, Mardziah; Robert, Penafort; Chong, Yip Boon (Elsevier, 2021)
Introduction: Sarcoidosis is a systemic granulomatous disease of unknown etiology, with a heterogenous clinical manifestation, progression, and prognosis. A combination of clinical, radiological, biochemical, and pathological findings is needed for accurate diagnosis. Case report: Herein, we present a young male presenting with acute back pain, initially suspicious of malignancy, with an eventual diagnosis of vertebral sarcoidosis; with sacrum, pelvic bone, and cutaneous involvement (Darier-Roussy disease), as well as associated mediastinal and abdominal lymphadenopathy. Following the diagnosis of vertebral sarcoidosis with associated Darier-Roussy disease, the patient was offered treatment but was not keen at the time of diagnosis. An outpatient appointment to re-discuss treatment options was given, should it be pursued. Conclusion: Vertebral sarcoidosis with associated Darier-Roussy disease is an extremely rare clinical entity, with multiple differential diagnoses. Pathological examination is confirmatory and should be pursued for accurate diagnosis and treatment.